Unilateral Surgery for Medullary Thyroid Carcinoma: Seeking for Clinical Practice Guidelines - Zhang, Daqi; Colombo, Carla; Sun, Hui; Kim, Hoon Yub; Pino, Antonella; De Leo, Simone; Gazzano, Giacomo; Persani, Luca; Dionigi, Gianlorenzo; Fugazzola, Laura (Frontiers in Endocrinology, 2022)
Optimized preoperative diagnostics with modern calcitonin tests, sonographic features, functional imaging modalities, and differential human genetic testing to detect hereditary forms have led to increased earlier diagnosis and surgery for medullary thyroid cancer (MTC). This helps to adapt the primary surgery to the tumor stage and avoid surgical overtreatment for localized tumor growth, i.e., deviating from the regularly recommended thyroidectomy with bilateral central lymph node dissection in favor of a limited unilateral approach. To limit primary surgical therapy, it is crucial that the MTC is clinically unifocal and sporadically confined to the thyroid and that calcitonin levels indicate biochemical recovery after surgery. The main structural requirement for such a limited approach is the low-threshold availability of frozen section studies that reliably indicate (i) R0 resection of the MTC, (ii) absence of infiltration of the organ capsule, (iii) lack of desmoplasia (i.e., evidence of the metastatic potential of the MTC), (iiii) absence of contralateral disease or precancerous lesions. Informed consent is mandatory from the patient, who has been fully informed of the advantages, disadvantages, and potential risks of not undergoing the procedure. The aim of this article is to review the guidelines for the management of early-stage MTC.